Intraperitoneal influx of neutrophils in response to IL-33 is mast cell-dependent. - FALLON, PADRAIC (My University, 2013)
IL-33 is a recently discovered cytokine involved in induction of Th2 responses and functions as an alarmin. Despite numerous recent studies targeting IL-33, its role in vivo is incompletely understood. Here we investigated inflammatory responses to intraperitoneal IL-33 injections in wild-type and mast cell-deficient mice. We found that wild-type mice, but not mast cell-deficient W(sh)/W(sh) mice, respond to IL-33 treatment with neutrophil infiltration to the peritoneum, whereas other investigated cell types remained unchanged. In W(sh)/W(sh) mice, the IL-33-induced innate neutrophil response could be rescued by local reconstitution with wild-type but not with T1/ST2(-/-) mast cells, demonstrating a mast cell-dependent mechanism. Furthermore, we found this mechanism to be partially dependent on mast cell-derived TNF, as we observed reduced neutrophil infiltration in W(sh)/W(sh) mice reconstituted with TNF(-/-) bone marrow-derived mast cells compared with those reconstituted with wild-type bone marrow-derived mast cells. In agreement with our in vivo findings, we demonstrate that human neutrophils migrate toward the supernatant of IL-33-treated human mast cells. Taken together, our findings reveal that IL-33 activates mast cells in vivo to recruit neutrophils, a mechanism dependent on IL-33R expression on peritoneal mast cells. Mast cells activated in vivo by IL-33 probably play an important role in inflammatory reactions.
PUBLISHED
Keywords: IL-33; Immunology, Inflammation & Infection; Biomedical sciences